Design and fabrication of multiplex microfluidic LAMP PCR for simultaneous detection of opportunistic protozoa - Fatemeh Mahdavi; Maryam Niyyati; Amir Shamloo; Rasool Dezhkam; Seyed Mohammadali Hoseinian; Seyyed Javad Seyyedtabaei; Hamed Mirjalali (Sensing and Bio-Sensing Research)
Intestinal parasites are a health problem in many regions, especially in developing countries. Giardia lamblia, Cryptosporidium spp., and Enterocytozoon bieneusi are of great diagnostic importance, particularly in immunocompromised patients and children. This study aimed to develop a multiplex microfluidic LAMP (MμLAMP) PCR for rapid detection of three protozoa. The LAMP primers were designed for the parasites. The microfluidic disk with different compartments was designed using AutoCAD software and fabricated by laser beam. After DNA extraction, the amplifications were performed for all positive samples using MμLAMP PCR. Sensitivity and specificity of tests were calculated and the results were compared to the real-time PCR. The LAMP analysis revealed that 29/30 (96.7 %), 12/19 (63.2 %), and 25/30 (83.3 %) samples were positive for G. lamblia, Cryptosporidium spp., and E. bieneusi, respectively. The specificity results of the LAMP method were high and the sensitivity test results indicated that the LAMP method has the ability to detect 180 ag/μL of G. lamblia DNA, 2.5 fg/μL of Cryptosporidium spp. DNA, and 34 ag/μL of E. bieneusi DNA. The multiplex accuracy results of microfluidic disk showed that none of two-parasite DNA mixes with their non-specific primers cause false positive results. The present study simultaneously detects G. lamblia, Cryptosporidium spp., and E. bieneusi. The current results indicate that the MμLAMP PCR method is a rapid, sensitive, and highly specific method for simultaneous detection of G. lamblia, Cryptosporidium spp., and E. bieneusi in clinical studies, making it a suitable tool for screening and point of care (PoC) testing.